Peningkatan Nilai Ekonomi Hasil Perikanan: Pengembangan Bisnis Produk Olahan Berbasis Ikan Lele (Clarias Spp) - Leila Ariyani Sofia; Rizmi Yunita (Universitas Lambung Mangkurat, 2021)
The purpose of this PKM is to provide knowledge and skills for catfish-based product processing, to know the driving and inhibiting factors for business sustainability, and to analyze the financial value of the business. The activity methods applied are: (1) socialization and theoretical learning, (2) training and mentoring, and (3) evaluation of activities. The results of the PKM showed that the attitudes and knowledge of Poklahasar members have increased from insufficient to sufficient about catfish-based processing. Variations in the knowledge and abilities of group members before and after counseling were decreasing or tending to the average score. The driving factor for the success of the activities and the sustainability of their respective businesses is the willingness of the group members to increase the quality and quantity of the processed product. Meanwhile, the inhibiting factor is the uncertainty of market demand so that the group only produces relatively limited quantities. The processing of catfish-based products is financially able to provide decent benefits with payback period is shortly.